Mobile Application: Inductions in a Retail Company - Gordillo Tenorio, Willy (2023)
Currently, most companies have an induction process whenever they hire a new employee. This implies a constant expense, but for some companies, the induction process only consists of assigning one of the company's internal workers to be in charge of the new worker and teach him the functions that correspond to him; this usually causes the new worker to have a poor performance in the first month of work. This research aims to design a mobile application to improve the induction process and therefore improve the performance of new workers from the first month of work. The methodology used was Design Thinking, which allowed the evaluation of different ideas and then implementation in a solution, prioritizing the user experience and achieving the development of the mobile application. A test was conducted on a population of 43 users, using questionnaires to gather information on their experience, satisfaction, and application approval. As a result, the surveyed users showed a high level of acceptance with respect to the three dimensions of the application: design, effectiveness, and induction control.